Freirean pedagogy implications for the teaching of phenomenology in nursing: an experience report - Vinícius de Oliveira Muniz; Gilberto Tadeu Reis da Silva; Larissa Chaves Pedreira; Tânia Maria de Oliveira Menezes; Raúl Fernando Guerrero-Castañeda (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To report the learning experience of students in the discipline "Phenomenology, Formation and Research", and to analyze the pedagogic planning of its problematization in the process of construction of knowledge, in a strict sensu program in Nursing and Health. Method: Descriptive-analytic report of the learning plan offered and of the theoretical framework of the data, from a Freirean perspective. Results: The discipline was offered in the form of distance-education classes to six students and organized in three units: the first included five synchronous meetings and one asynchronous meeting; the second, three synchronous meetings; and the third, seven synchronous meetings and one asynchronous meeting. The methodologies applied included: presentations from guest lecturers, inverted classroom, and conceptual map. Husserl's and Heidegger's lines of thought were discussed. Conclusion: The construction of knowledge in phenomenology by postgraduates took place according with Freire's pedagogical structure, highlighting the concept of problematization.